The Use of 3D-Based E-Handout on Excretory System Material To Improve Students' Critical Thinking Skills - Sukroni, Nining Widiyanti; Kartimi, Kartimi; Mulyani, Asep; Marzuki, M. (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
Students' critical thinking skills in high school are still lacking. Learning media in textbooks is still less effective and interactive in the learning process. This study aims to analyze the improvement of students' critical thinking skills using 3D-based e-handout. This research is true-experiment research with a pretest-posttest control group design. The population in this study were all eleventh-grade Mathematics and Science major (MIPA) classes at SMAN 1 Ciwaringin, which consisted of 128 students. The samples were classes XI MIPA 1 and XI MIPA 2. This study showed a significant increase in students' critical thinking skills between experimental classes, with an average N-gain value of 0.60 (moderate category), and the control class, with an N-gain value of 0.28 (low category).ABSTRAK: Keterampilan berpikir kritis siswa di sekolah masih kurang. Media pembelajaran yang masih berupa buku paket kurang efektif dan interaktif dalam proses pembelajaran. Penelitian ini bertujuan untuk menganalisis peningkatan keterampilan berpikir kritis siswa menggunakan e-handout berbasis 3D. Penelitian ini merupakan jenis penelitian true-eksperimen dengan desain penelitian pretest-posttest control group design. Populasi dalam penelitian ini adalah seluruh kelas XI MIPA di SMAN A Ciwaringin berjumlah 128 siswa dan sampel yang digunakan adalah kelas XI MIPA 1 dan XI MIPA 2. Terdapat peningkatan keterampilan berpikir kritis siswa yang signifikan antara kelas eksperimen dengan rata-rata nilai N-gain kelas eksperimen 0,60 tergolong kedalam keriteria sedang sedangkan nilai N-gain kelas kontrol 0,28 tergolong kedalam kategori rendah.